1995
DOI: 10.1002/1097-0142(19950201)75:3<874::aid-cncr2820750320>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

High dose chemotherapy with ifosfamide, carboplatin, and etoposide combined with autologous bone marrow transplantation for the treatment of poor-prognosis germ cell tumors and metastatic trophoblastic disease in adults

Abstract: Background. A Phase I—II trial to assess the toxicity and efficacy of a tandem high dose chemotherapy combining ifosfamide, carboplatin, and etoposide in germ cell tumors and metastatic trophoblastic disease was performed. Methods. Thirty‐nine patients, with a total of 22 testicular tumors, 9 extragonadal germ cell tumors, 3 ovarian germ cell tumors, and 5 cases of metastatic trophoblastic disease, received tandem high dose therapy combining ifosfamide (7500‐12,500 mg/m2), carboplatin (875‐1225 mg/m2), and eto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0
2

Year Published

1995
1995
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(32 citation statements)
references
References 49 publications
2
28
0
2
Order By: Relevance
“…However, high-dose ICE exhibited the highest effectiveness among all the regimens the patient had received. Previous reports of high-dose ICE for intractable malignancies reported side effects, such as oral ulcers, esophagitis, nausea and diarrhea, in ~100% of the cases, and liver dysfunction and neurological disorders in ~30% of the cases (8). In terms of myelosuppression, 36% of the patients had infection or sepsis, and 18% succumbed due to severe side effects.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…However, high-dose ICE exhibited the highest effectiveness among all the regimens the patient had received. Previous reports of high-dose ICE for intractable malignancies reported side effects, such as oral ulcers, esophagitis, nausea and diarrhea, in ~100% of the cases, and liver dysfunction and neurological disorders in ~30% of the cases (8). In terms of myelosuppression, 36% of the patients had infection or sepsis, and 18% succumbed due to severe side effects.…”
Section: Discussionmentioning
confidence: 93%
“…After excluding male cases or non-gestational choriocarcinoma, our search yielded 21 cases in 11 articles between 1991 and 2013 (Table II) (7,8,(10)(11)(12)(13)(14)(15)(16)(17)(18). Two cases reported by Jean-Pierre Lotz in 1991 (11) were included in the 5 cases reported in 1995 by the same author (8).…”
Section: Hdc Diagnosis ----------------------------------------------mentioning
confidence: 99%
“…The high treatment-related mortality (17%) that occurred in our patient population before the availability of the colony-stimulating factors was similar to the mortality observed in other series during the same period. [31][32] However, with better patient selection and improved supportive care, the treatment-related mortality that occurred in our experience in the 1990s was 7%, compared with HDCT-related mortality data in GCT patients from the European Bone Marrow Transplantation Solid Tumors Registry. 33 No patient developed myelodysplasia or secondary leukemia after receiving HDCT, even though an increase was reported in other experiences.…”
Section: Discussionmentioning
confidence: 76%
“…The Table divides the studies based on the number of patients in each study reported to have extragonadal primaries, a prognostic factor known to have a poor outcome for response. 21,22 Several observations may be made from the results described in Table 5. In group A or the three studies that reported 33-45% incidence of extragonadal primaries in their patient pool (A1-A3: Refs 15-18), one or two cycles of HDC (of a two or three-drug regimen) resulted in a 34-45% EFS.…”
Section: Discussionmentioning
confidence: 99%
“…Patients who were still responsive to induction chemotherapy obtained the most benefit with a 77% eventfree survival at 4 years ( Figure 2, log-rank test, P value 0.0082). Using tandem HDC with ifosfamide/ carboplatin/etoposide and marrow transplantation, Lotz et al 22 showed only an 18% (5/28) long-term disease-free survival (10-84 months) in 28 germ cell tumor patients (18 testis, seven extragonadal, three ovarian) who were all refractory to cisplatin. Other investigators have also indicated the importance of cisplatin-refractoriness as a prognostic factor.…”
Section: Discussionmentioning
confidence: 99%